A perspectiva jurídico-ecológica a partir de uma ecocidadania: o vínculo homem-natureza e o direito - Sass, Liz Beatriz (Universidade do Vale do Rio do Sinos, 2006)
This present research proposes a reflection about the relation man-nature in the legal context. So, in the first chapter, the theoretical fundament is sought among the philosophers of the Ionian School and in the modern thought, whose content in the scope of this research is dialogued with René Descartes, Francis Bacon, Thomas Hobbes and Immanuel Kant. Thus, it is tried to make evident the way we relate with nature adopted, in the first moment, by the Greeks and, in a second moment, by the Modern ones, whose transition between one and the other shows the rupture of the connection man-nature in Modernity. From this point, in the second chapter, it is verified how this rupture shows itself through the legal dogmatic speech. Due to an emergency of an ecological perspective, it makes evident the introduction of the Environmental Law in the Brazilian legal system. However, it is shown, in the third chapter, the symbolic function of the legal speech that protects the environment. It is then introduced, an ecocitiz
Keywords: direito ambiental; ecocidadania; ecologia; ecocitizenship; ecology; law; Ciências Sociais Aplicadas